POLITENESS STRATEGIES USED BY TOBA BATAK SELLERS IN BANDUNG DISTRICT WEST JAVA, KOSAMBI AND CIROYOM TRADITIONAL MARKET: An Action Research of Language Analysis (English Literature Study Program of Universitas Kebangsaan Republik Indonesia, 2023)
This study deals with politeness strategies used by toba batak sellers in Kosambi and Ciroyom districts traditional market. The objectives of this study were (1) to describe the types of politeness strategies were used by Toba Batak sellers in West Java, (2) to investigate the type of politeness strategy was mostly used describe the reasons, (3) to describe the roles of politeness to Toba Batak society, and (4) to describe the implication of politeness strategies. The data of this study were the language of conversation between Toba Batak sellers and their buyers. This study applied descriptive quantitative method. The findings show that there are four types of Politeness Strategies used by Toba Batak Sellers in West Java district such as Dago and Kosambi traditional market, namely: Bald on record4 utterances (2.53%), Off record17 utterances (10.75%), Positive politeness 129 utterances (81.64%) and Negative politeness 8 utterances (5.06%). Positive politeness is the most dominant type of Politeness Strategies used by Toba Batak sellers in district West Java Bandung.